Penerapan Model Pembelajaran Project Based Learning terhadap Pengetahuan dan Keterampilan Materi Bumbu Dasar - Defia Laili Mustafik Putri; Asrul Bahar; Niken Purwidiani; Mauren Gita Miranti (Pusat Riset dan Inovasi Nasional, 2023)
This study aims to determine the application of the Project Based Learning (PjBL) learning model on basic seasoning material to the knowledge and skills of grade X culinary students at SMKN 1 Cerme Gresik. This study used a type of Quasi-Experimental research using a Post-test Only Control Group Design research design. Data were obtained using Post-Test questions and assessment sheets of the results of the practice of making basic and processed seasonings. Data analysis techniques were carried out with the Independent Sample T-Test and Mann-Whitney test with the help of the SPSS 25 program. The results showed that the average value of knowledge and skills of the experimental class was higher than that of the control class. Based on the results of the Independent T-Test Asymp. Sig. (2-tailed) from the post-test value for the experimental class, which is 0.000, there is an influence of the application of the Project Based Learning (PjBL) learning model on the results of student knowledge of basic seasoning material. While the skill results are based on the Mann-Whitney Asymp test. Sig. (2-tailed) from the practice value of making basic seasoning of 0.000, there is an influence of the use of the Project Based Learning (PjBL) model on the results of psychomotor skills in basic seasoning material.